Thermotolerant Coliform Die-off in Water Treated with Moringa Oleifer A SEEDS - Costa, Renata Albuquerque; Silva, Giselle; Peixoto, Jackson; Silva, Regine (Ciência e Natura, 2014)
The objective of this study was to test the ability of moringa seeds (Moringa oleifera) to eliminate thermotolerant coliforms (TTC) in water samples from a contaminated river in Northeastern Brazil (Rio Acaraú, Sobral). The treatment was administered in two concentrations: 5 g (T1) and 10 g (T2) homogenized seeds/1000 mL water. Twenty water samples were shaken continuously for 60 min and aliquots were drawn at 10, 20, 30 and 60 min to determine the most probable number of TC. The greatest die-off (99.9%) was observed for T1 at 20 min. Our findings show that moringa seeds are an effective means of eliminating coliforms and may be employed in bacterial decontamination of water bodies.